Analyzing Korean elementary school teachers’ arm muscle models as scientific models - Kım, Dongryeul (Journal of Turkish Science Education, 2024)
The aim of this study was to analyze pre-service elementary school teachers’ Arm Muscle models and elementary school teachers' evaluation viewpoints of their Arm Muscle models as scientific models. The sample of this study consisted of 24 pre-service elementary school and 12 elementary school teachers. Preservice elementary school teachers, who were divided into three groups, directly developed 3 Arm Muscle models. 12 elementary school teachers evaluated their developed 3 Arm Muscle models as scientific models. Most of elementary school teachers suggested that three models helped pre-service elementary school teachers conceptually understand the relationship between muscles and bone. Also, the results indicated that pre-service elementary school teachers made three models by visually imitating the shapes of real bone and muscle tendons. Further, elementary school teachers evaluated pre-service elementary school teachers' efforts given visual similarities between actual bone and muscle tendons Most of elementary school teachers addressed that these 3 Arm Muscle models were practically good at acting as an automatic model. The current study recommends that modifying these models may increase their scientific values in the future.
Keywords: Arm Muscle models; elementary teachers; science education; scientific models